RAGAM BAHASA DALAM INTERAKSI JUAL BELI DI KOMPLEKS PALU PLAZA - Risma, Risma; Zulianto, Sugit; Harisah, Sitti (BAHASANTODEA, 2017)
This research aims at describing the diversity and the function of languages used in the interaction of selling and buying in complex of Palu Plaza, and factor caused the language diversity. Data source were obtained through verbal utterances of seller and buyer in complex of Palu Plaza by using study of communication ethnography. Method used in this research is qualitative descriptive. Data were collected through four techniques: recording, field-note, observation, and interview unstructured. Subject of this research is the seller and the buyer in Palu Plaza. Technique of data analysis used is interactive model that covers four stages: data collection, data reduction, data presentation, and conclusion and verification. The result of this research revealed that the language diversity used in the interaction between seller and buyer in Palu Plaza is: (1) the form of word use, (2) the use of phrase, (3) the use of sentence. Functions of language diversity found in this research are: (1) emotive function, (2) fatigue function, and (3) directive function. Factors caused the diversity are: (1) age factor, (2) factor of regional origin, (3) gender factor, (4) education factor, (5) factor of occupation/profession, and (6) factor of social status.